Lean in healthcare: A comprehensive review - D’Andreamatteo, Antonio; Ianni, Luca; Lega, Federico; Sargiacomo, Massimo (Health policy (Amsterdam), 2015)
•We aim to provide a comprehensive review of Lean in healthcare.•Lean is an improvement approach increasingly applied in healthcare.•Notwithstanding the growing body of knowledge some issues remain underexplored.•Evaluation of more “system wide approach” in its implementation is needed. Lean seems to be the next revolution for a better, improved, value-based healhcare. In the last 15 years Lean has been increasingly adapted and adopted in healthcare. Accordingly, Lean healthcare has been developing into a major strand of research since the early 2000s. The aim of this work is to present a comprehensive overview of the main issues highlighted by research on implementation of Lean in a complex contest such as the healthcare one. Comprehensive literature review was conducted in order to identify empirical and theoretical articles published up to September 2013. Thematic analysis was performed in order to extract and synthesis data. 243 articles were selected for analysis. Lean is best understood as a means to increase productivity. Hospital is the more explored setting, with emergency and surgery as the pioneer departments. USA appears to be the leading country for number of applications. The theoretical works have been focused mainly on barriers, challenges and success factors. Sustainability, framework for measurement and critical appraisal remain underestimated themes. Evaluations of “system wide approach” are still low in number. Even though Lean results appear to be promising, findings so far do not allow to draw a final word on its positive impacts or challenges when introduced in the healthcare sector. Scholars are called to explore further the potentiality and the weaknesses of Lean, above all as for the magnitude of investments required and for the engagement of the whole organization it represents increasingly strategic choice, whilst health professionals, managers and policy makers could and should learn from research how to play a pivotal role for a more effective implementation of lean in different health contexts.